Do Adolescents with Gynecomastia Require Routine Evaluation by Endocrinology?. Issue 1 (July 2018) - Malhotra, Armaan K.; Amed, Shazhan; Bucevska, Marija; Bush, Kevin L.; Arneja, Jugpal S.
Abstract : Background: Primary evidence for the role of endocrinologic investigations in patients with adolescent gynecomastia is lacking in the current literature. The objective of this study was to assess the yield of endocrinologic investigations in the evaluation of adolescent gynecomastia to inform current practice for this common condition. Methods: A 26-year retrospective review was conducted. Data collection included patients with gynecomastia presenting to endocrinology at a quaternary children's hospital with a catchment area of 1 million. Clinical metrics, endocrinologic results, treatments, and costs were reviewed. Results: One hundred ninety-seven patients met inclusion criteria. Ninety-eight (50 percent) were overweight or obese and 29 (15 percent) had a positive family history. The median age at onset was 11.5 years; 25 cases (13 percent) were prepubertal. A total of 15 patients (7.6 percent) were diagnosed with secondary gynecomastia (10 related to exogenous substance use). Endocrine investigations were performed in 173 patients (87 percent), with positive findings in three cases (1.7 percent). One hundred one patients were observed, with a median age at resolution of 14.6 years; 86 patients underwent surgery at a median age of 16.5 years. The case-cost of endocrine evaluation was $389. Conclusions: Endocrinologic workup identified secondary gynecomastia in 7.6 percent of patients, of which only 1.7 percent were evident on blood work. This workup is associated with an avoidable case-cost burden to the health care system and largely unnecessary testing for the child. Because a majority of secondary gynecomastia cases (67 percent) were drug-induced, we do not suggest routine endocrinology workup, as it adds little value. The authors' data suggest that referral for surgery is warranted if gynecomastia persists beyond 16 years of age. CLINICAL QUESTION/LEVEL OF EVIDENCE: Diagnostic, IV. Abstract : This and Related "Classic" Articles Appear on Prsjournal.com for Journal Club Discussions.